Effect Of Stem Integrated Physics E-Modules To Improve Creative Thinking Ability - febbi rahmadani; Festiyed Festiyed; Asrizal Asrizal; Desnita Desnita (Universitas Negeri Padang, 2023)
The Industrial Revolution 4.0 is an era of rapid development and technology. This era requires the ability to higher order thinking to prepare participants for development. Based on the demands of Time for national education issued an effort to increase the curriculum to the 2013 curriculum to stimulate participants to educate. The 2013 curriculum sets graduate competency standards based on student readiness, national education goals, and needs. Updating the learning process is urgently needed, one of which is by adjusting the teaching materials used for the material to be delivered. In the learning process, the main component is the availability of teaching materials that will be used by students. There are teaching materials in the form of print and non-print. The purpose of this study was to see the effect of the STEM Integrated Physics E-Module to improve the Creative Thinking Ability of Class XI Students of. This research method uses a quasi-experimental design using the posttest only design. After conducting the research it turned out that students' creative thinking abilities as seen from each student's answer from the two sample classes had different averages in common, namely the normality test, test homogeneity, two-mean similarity test From the analysis results obtained, namely the value of th is in the H0 resistance area so that it can be said that H1 is accepted at a significant level of 0.05. The results of the statistical analysis of the data show that th> tt is 2,764473449> 1,67528495042491, so it can be concluded that there are differences in students' creative thinking skills in the aspect of knowledge using e-modules and not using e-modules.